An Analysis of Cost Efficiency and Loan Loss Provisioning Behaviour in Hong Kong Commercial Banks - Latheef, Fathmath Aroosha (2015)
This study examines Cost Efficiency and Loan loss provisioning in Hong Kong commercial banks between the years 2009-2014 for a sample of 23 banks. While much research explores discretionary provision determinants we argue that it is also important to access non-discretionary determinants of loan loss provisioning as well. So along with income smoothing, capital management hypothesis we further investigate cost efficiency and bank insolvency (Z-score) as possible determinants of loan loss provisions. To do so we use Cost efficiency function using SFA and a dynamic system GMM is used for Loan loss provisions model. We find that for Hong Kong commercial banks Counter-cyclical provisioning, capital management hypothesis apply and Efficiency is an important determinant of loan loss provisions in Hong Kong.